2015
DOI: 10.4236/psych.2015.615197
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Personality Traits and Age on Academic Self-Handicapping among Undergraduate Students of Ahmadu Bello University, Zaria, Nigeria

Abstract: The present study examined the differences in academic self-handicapping among undergraduate students based on personality traits and age. Participants (N = 440) completed two questionnaires-Big Five Inventory and Self-handicapping Scale. Analysis of data reveals that significant negative correlation exists between academic self-handicapping of undergraduates and their next personality traits-agreeableness, conscientiousness and openness to new experience (with r = −.322, −.317 and −.161 respectively), while w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…If the situation is good, individuals can say that they overcame the handicap in his ability. The second functions help to deal with the expected weak performance (Litvinova, Balarabe & Mohammed, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the situation is good, individuals can say that they overcame the handicap in his ability. The second functions help to deal with the expected weak performance (Litvinova, Balarabe & Mohammed, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A basic principle of self-handicapping is the principle of discounting and increasing. The principle of deduction refers to the fact that when the individual handicap himself in a particular task and provides an excuse for failure, it reduces the failure rates because of its efficiency and gives it an excuse (Litvinova, Balarabe & Mohammed, 2015). The principle of increase indicates that if success occurs despite the presence of obstacles, it indicates the efficiency of the individual, and the increase is because the good performance occurred despite the existence of obstacles that leads to the promotion of self-esteem has (Wusik, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A sample of 440 participants completed two questionnaires, Big Five Inventory and Self-handicapping Scale. Analysis of data reveals that significant negative correlation exists between academic self-handicapping and their personality traits-agreeableness, conscientiousness and openness to new experience, while for neuroticism this correlation is positive (Litvinova et al, 2015).…”
Section: Review Of Literaturementioning
confidence: 93%
“…Based on personality traits, another study by Litvinova et al (2015) studied the differences in academic self-handicapping among undergraduate students. A sample of 440 participants completed two questionnaires, Big Five Inventory and Self-handicapping Scale.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Numerous studies have suggested that a relationship exists between SES and academic self-handicapping behaviors. For instance, (a) students from mothers who have low educational levels, (b) students from single family parents, (c) students from larger families, and (d) last-born in the family show higher levels of self-handicapping behaviors (Dinnel, Hopkins, & Thompson, 2002;Fahey, Keilthy, & Polek, 2012;Litvinova, Balarabe, & Mohammed, 2015;Strickland, 2001).…”
Section: Age Race and Socioeconomic Statusmentioning
confidence: 99%